Peri-implant clinical profile and subgingival yeasts carriage among cigarette-smokers with peri-implant mucositis - Asmaa Saleh Almeslet; Suha Mohammed Aljudaibi (BMC, 2024)
Abstract Background The present observational clinical investigation is based on the hypothesis that subgingival yeast carriage (SYC) is higher in cigarette-smokers with peri-implant mucositis (PM) than non-smokers with and without PM. Objective The aim was to assess peri-implant clinical profile and SYC among cigarette-smokers with PM. Methodology Participants were divided into four groups: Group-1-Cigarette-smokers with PM; Group-2-Cigarette-smokers without PM; Group-3-Non-smokers with PM; and Group-4-Non-smokers without PM. Information on duration and daily frequency of cigarette smoking (pack years), age, gender, familial history of smoking and most recent visit to a dentist and/or dental hygienist was collected. The following information was retrieved from healthcare records: implant dimensions, implant insertion torque, depth of insertion (credidastal or subcrestal), implant abutment connection, jaw location, implant surface characteristic, and mode of implant prosthesis retention. Peri-implant modified plaque and gingival indices (mPI and mGI), probing depth (PD) and crestal bone loss were recorded. Subgingival biofilm samples were collected, and SYC was recorded in colony forming units per milliliter (CFU/ml). P < 0.05 were considered statistically significant. Results Eighty male individuals (20, 19, 21 and 20 individuals were included in groups 1, 2, 3 and 4, respectively) were included. The mPI was higher in Group-1 than groups 2 (P < 0.05) and 4 (P < 0.05). The mPI was higher in Group-3 than groups 2 (P < 0.05) and 4 (P < 0.05). The mGI was higher in Group-3 than groups 1 (P < 0.05), 2 (P < 0.05) and 4 (P < 0.05). The PD was higher in Group-1 than groups 2 (P < 0.05) and 4 (P < 0.05). The PD was higher in Group-3 than Groups 2 (P < 0.05) and 4 (P < 0.05). The CFU/ml were higher in Group-1 than groups 2 (P < 0.05) and 4 (P < 0.05). The CFU/ml were higher in Group-3 than groups 2 (P < 0.05) and 4 (P < 0.05). Conclusion Peri-implant soft-tissue inflammatory parameters are worse and SYC is higher in moderate smokers than light smokers with PM and non-smokers without PM.